"Is It All Right for Me to Have a Baby or Not?": Men Living With HIV Discuss Fertility Desires and Interactions With Providers. (January 2017) - Weber, Shannon; Zakaras, Jennifer M.; Hilliard, Starr; Cohan, Deborah; Dworkin, Shari L.
Abstract : N/A: To our knowledge, no study in the United States has qualitatively examined fertility desires, experiences communicating with health care providers about sexual and reproductive health, and attitudes toward reproductive counseling and services in men living with HIV (MLWH) who have sex with women. We conducted focus groups and interviews with MLWH ( N = 17) who have sex with women seeking HIV care in San Francisco. The men conveyed limited awareness of safer conception strategies. While many men expressed the desire to have a child, most reported that their providers had not discussed reproduction with them. Participants highlighted the lack of HIV services for men who have sex with women and the need for improved reproductive counseling. We make recommendations for providers who work with MLWH who have sex with women and for patient‐centered materials on safer conception, sexual HIV transmission risk reduction, and family planning strategies.